Persistent defensive reactivity during extensive avoidance training as a potential mechanism for the perpetuation of safety behaviors - Joscha Franke; Christiane A. Melzig; Christoph Benke (Scientific Reports)
Abstract Safety behaviors are core features of anxiety-related disorders, specifically involving behaviors that do not completely terminate aversive situations, but rather prevent the risk of the occurrence of the expected aversive outcome (US). This study aimed to examine the dynamics of defensive reactivity associated with safety behaviors, both before and after their execution, and to investigate changes in these reactions following extensive training. Twenty-four healthy participants underwent a US-avoidance task as an experimental analog to model safety behavior, requiring a button press to avoid the US without terminating the associated warning cue (CS). Two CS+ were used, with one being devalued during a devaluation procedure to assess the formation of avoidance habits. Defensive reactivity was assessed using fear-potentiated startle (FPS) and skin conductance responses (SCR). Participants showed pronounced defensive reactivity to both CS + vs. CS- before the avoidance action, which decreased upon the opportunity to avoid the US. Contrarily, after the avoidance action, a re-emergence of defensive responses was observed as indicated by FPS and increased SCR. Only one participant showed signs of avoidance habit formation. The findings reveal a re-emergence of defensive reactivity following safety behaviors challenging the prevailing belief that relief is the primary sustaining factor of safety behavior.